2018
DOI: 10.21608/ejabf.2018.20507
|View full text |Cite
|
Sign up to set email alerts
|

Physa acuta snail as a biomonitor for the efficacy of bioremediation treatment of heavy metals (Fe III and Cd II) using the fungus (Eupenicillium lapidosum) in lined and unlined laboratory conditions

Abstract: lipid peroxidation (MDA) and decrease of endogenous antioxidant enzymes; Catalase (CAT) and glutathione (GSH) in lined conditions than that of unlined ones, while the effect decreased in the case of Fe and Cd biosorption. So, these results indicated that P. acuta snail and the fungus E. lapidosum are useful in the searches for biomarkers and biosorption, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…For example, Physa acuta was shown to be a suitable bioindicator of metal toxicity under laboratory conditions [61]. Subsequent research has confirmed this species to be useful for metal bio-uptake research [62]. In addition, Lymnaea stagnalis was reported to be one of the most sensitive species to a 96 h copper exposure [53], and a good bioindicator of mercury contamination in aquatic ecosystems [63].…”
Section: Bioaccumulation Of Metalsmentioning
confidence: 99%
“…For example, Physa acuta was shown to be a suitable bioindicator of metal toxicity under laboratory conditions [61]. Subsequent research has confirmed this species to be useful for metal bio-uptake research [62]. In addition, Lymnaea stagnalis was reported to be one of the most sensitive species to a 96 h copper exposure [53], and a good bioindicator of mercury contamination in aquatic ecosystems [63].…”
Section: Bioaccumulation Of Metalsmentioning
confidence: 99%